Long-term safety and efficacy of closed-loop spinal cord stimulation to treat chronic back and leg pain (Evoke): a double-blind, randomised, controlled trial. Issue 2 (February 2020) - Mekhail, Nagy; Levy, Robert M; Deer, Timothy R; Kapural, Leonardo; Li, Sean; Amirdelfan, Kasra; Hunter, Corey W; Rosen, Steven M; Costandi, Shrif J; Falowski, Steven M; Burgher, Abram H; Pope, Jason E; et al.
Summary: Background: Spinal cord stimulation has been an established treatment for chronic back and leg pain for more than 50 years; however, outcomes are variable and unpredictable, and objective evidence of the mechanism of action is needed. A novel spinal cord stimulation system provides the first in vivo, real-time, continuous objective measure of spinal cord activation in response to therapy via recorded evoked compound action potentials (ECAPs) in patients during daily use. These ECAPs are also used to optimise programming and deliver closed-loop spinal cord stimulation by adjusting the stimulation current to maintain activation within patients' therapeutic window. We aimed to examine pain relief and the extent of spinal cord activation with ECAP-controlled closed-loop versus fixed-output, open-loop spinal cord stimulation for the treatment of chronic back and leg pain. Methods: This multicentre, double-blind, parallel-arm, randomised controlled trial was done at 13 specialist clinics, academic centres, and hospitals in the USA. Patients with chronic, intractable pain of the back and legs (Visual Analog Scale [VAS] pain score ≥60 mm; Oswestry Disability Index [ODI] score 41–80) who were refractory to conservative therapy, on stable pain medications, had no previous experience with spinal cord stimulation, and were appropriate candidates for a spinal cord stimulation trial were screened. Eligible patients were randomly assigned (1:1) to receive ECAP-controlled closed-loop spinal cord stimulation (investigational group) or fixed-output, open-loop spinal cord stimulation (control group). The randomisation sequence was computer generated with permuted blocks of size 4 and 6 and stratified by site. Patients, investigators, and site staff were masked to the treatment assignment. The primary outcome was the proportion of patients with a reduction of 50% or more in overall back and leg pain with no increase in pain medications. Non-inferiority (δ=10%) followed by superiority were tested in the intention-to-treat population at 3 months (primary analysis) and 12 months (additional prespecified analysis) after the permanent implant. This study is registered with ClinicalTrials.gov, NCT02924129, and is ongoing. Findings: Between Feb 21, 2017, and Feb 20, 2018, 134 patients were enrolled and randomly assigned (67 to each treatment group). The intention-to-treat analysis comprised 125 patients at 3 months (62 in the closed-loop group and 63 in the open-loop group) and 118 patients at 12 months (59 in the closed-loop group and 59 in the open-loop group). The primary outcome was achieved in a greater proportion of patients in the closed-loop group than in the open-loop group at 3 months (51 [82·3%] of 62 patients vs 38 [60·3%] of 63 patients; difference 21·9%, 95% CI 6·6–37·3; p=0·0052) and at 12 months (49 [83·1%] of 59 patients vs 36 [61·0%] of 59 patients; difference 22·0%, 6·3–37·7; p=0·0060). We observed no differences in safety profiles between the two groups. The most frequently reported study-related adverse events in both groups were lead migration (nine [7%] patients), implantable pulse generator pocket pain (five [4%]), and muscle spasm or cramp (three [2%]). Interpretation: ECAP-controlled closed-loop stimulation provided significantly greater and more clinically meaningful pain relief up to 12 months than open-loop spinal cord stimulation. Greater spinal cord activation seen in the closed-loop group suggests a mechanistic explanation for the superior results, which aligns with the putative mechanism of action for spinal cord stimulation and warrants further investigation. Funding: Saluda Medical.